Surgical vs. nonsurgical management of post-traumatic intercostal lung herniation in children - Mila Kolar; Ayca Toprak; Andrea Winthrop; Lloyd Sly; Donald Soboleski (Elsevier, 2018)
Background: Intercostal lung herniation (ILH) is an exceptionally rare condition in pediatric patients, characterized by disruption of fascial planes and intercostal musculature allowing for protrusion of a portion of the lung parenchyma into this space. In most cases it is a consequence of blunt chest trauma. Due to the rarity of the condition, diagnostic and management approaches are based on the experience in adults, where CT is the most often used diagnostic tool, and surgery is the primary management approach. Recent published experience in adult and pediatric patients supports the use of less invasive imaging and management strategies, particularly in otherwise asymptomatic patients, giving us the opportunity to reconsider our clinical approaches in the diagnosis and management of these patients. Methods: We present a recent case of posttraumatic ILH. In addition, we conducted a systematic review of the literature. A search of the PubMed, Embase, Ovid, Scopus and Cochrane databases was conducted using a combination of the following search terms: intercostal lung hernia in children, lung herniation in children, traumatic intercostal lung hernia in children. Two authors independently extracted data, reviewed the abstracts, and assessed them for inclusion in the review. Results: All reported cases were single case reports, with total of 16 including our patient. All ILH were unilateral. The most common etiology was bicycle handle bar injury 10 (63%). Herniation was found on the anterior chest wall in 13 (81%) patients, and in 3 (19%) was on the anterolateral chest wall. To confirm the diagnosis chest x-ray was used in 14 (88%) patients, CT chest in 7 (44)%, fluoroscopy in 1 (6%), chest ultrasound in 3 (19%), and in 1 patient there was no imaging documented. Management was surgical in 10 patients (63%) including thoracotomy with primary closure in 8 patients and thoracoscopic repair in 2 patients. Six patients (37%) had nonsurgical management by chest strapping, with complete resolution of herniation within 2â6 weeks. There was no reported complications or recurrence following either type of management. Conclusions: Postraumatic intercostal lung herniation in children is a rare condition. Including our case reported here, there are only 16 reported cases. In children ILH is mostly seen after blunt chest trauma caused by bicycle handle bar injury. Given the rarity of the condition, the pediatric literature on this subject is scarce, with no published guidelines or evidence based recommendations for imaging and management approaches (surgical vs. nonsurgical). Although rare, the pediatric surgeon should be familiar with this condition in order to avoid potentially harmful, invasive or unnecessary diagnostic and therapeutic approaches that are extrapolated from experience in adult patients. Noninvasive imaging modalities including chest radiographs and ultrasound, and nonsurgical management of posttraumatic intercostal lung herniation should be considered as an initial treatment option in the management of asymptomatic patients.